Editorial: uma vela para a navegação - Novaes, Sylvia Caiuby; Barbosa, Andrea; Cunha, Edgar Teodoro da; Giesbrecht, Érica; Barbosa, Francirosy Campos; Dawsey, John Cowart; Lopes, Paula Morgado Dias; Hikiji, Rose Satiko G.; Grunvald, Vi (GIS - Gesto, Imagem e Som - Revista de Antropologia, 2023)
Editorial do Volume 8 da GIS - Gesto, Imagem e Som - Revista de Antropologia.